Pentazocine induced ulcers: a presentation of drug abuse - Shah, Nidhi; Paudel, R (Journal of BP Koirala Institute of Health Sciences, 2018)
Not available. Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, Page: 75-77